Pengaruh Service Quality, Digital Technology pada Customer Perceived Value dan Perceived Trust pada PT Pupuk Indonesia Holding Company - Zoel Hutabarat (Faculty of Economics and Business Universitas Pelita Harapan, 2023)
This study aims to examine the effect of interaction quality, outcome quality and environmental quality on customer perceived value which is moderated by digital technology and ultimately affects consumer trust. The object of the company in this study is PT Pupuk Indonesia Tbk with the respondents being distributor companies, farmer groups or cooperatives that place orders for subsidized fertilizers produced by the company. The form of this research is quantitative research by distributing questionnaires to 200 respondents spread throughout Indonesia. Questionnaire data will be processed using Smart PLS. The results of this study indicate that digital technology has not been utilized by distributors and farmer groups so that the digital technology variable has no effect on customer perceived value. Including digital technology variable as a moderator does not have an impact on strengthening or weakening the relationship between interaction quality, outcome quality and environment quality variables on customer perceived value. Outcome quality and environment quality variables have a direct effect on customer perceived value and customer perceived value influences perceived trust.Bahasa Indonesia Abstrak: Penelitian ini bertujuan untuk melihat pengaruh kualitas interaksi, kualitas hasil dan kualitas lingkungan terhadap nilai yang dirasakan pelanggan yang dimoderasi oleh teknologi digital dan pada akhirnya mempengaruhi kepercayaan konsumen. Objek perusahaan dalam penelitian ini adalah PT Pupuk Indonesia Tbk dengan responden adalah perusahaan distributor, kelompok tani atau koperasi yang melakukan pemesanan pupuk bersubsidi yang diproduksi oleh perusahaan. Bentuk penelitian ini adalah penelitian kuantitatif dengan menyebarkan kuesioner kepada 200 responden yang tersebar di seluruh Indonesia. Data kuesioner akan diolah menggunakan Smart PLS. Hasil penelitian ini menunjukkan bahwa digital technology belum dapat dimanfaatkan oleh distributor dan kelompok tani sehingga variabel digital technology tidak berpengaruh terhadap customer perceived value. Termasuk juga variabel digital technology sebagai moderator tidak memberi dampak memperkuat atau memperlemah hubunngan antara variabel interaction quality, outcome quality dan environment quality terhadap customer perceived value. Variabel outcome quality dan environment quality berpengaruh secara langsung terhadap customer perceived value dan customer perceived value berpengaruh terhadap perceived trust.